STUDY OF ELECTROLYTES AND LIVER FUNCTION TESTS IN CHRONIC ALCOHOLISM - Gill, Gurpreet Kaur; Kataria, Juhi; Singh, Amandeep; Thakur, Lalit; Kaur, Daljit (Asian journal of pharmaceutical and clinical research, 2018)
Objective: Alcohol abuse is considered one of the major health issue in India, which can impair the electrolyte balance in chronic patient of alcoholism. In the present study, investigation has been conducted to estimate the levels of calcium, magnesium, SGOT, SGPT, total protein and urea in the chronic alcoholic patients and their comparison was determined with normal healthy controls.Methods: A total of 50 male alcoholics consuming variable amount of alcohol from more than past 5 years in the age frame of 30–70 years were taken. Equal number of age-matched normal healthy individuals without the family history of any disease served as controls. Levels of magnesium (Mg), calcium (Ca), and other biochemicals, namely urea and total protein, transaminases, namely serum glutamate oxaloacetate transaminase and serum glutamate pyruvic transaminase were estimated colorimetrically in all the subjects consuming variable amount of alcohol.Results: Alcoholics were found to have lower magnesium, calcium, and total protein levels as compared to non-alcoholics, whereas transaminases were higher in alcoholics, predicting hepatocytes injury. Catalytic activity of alcohol dehydrogenase produced highly reactive acetaldehyde forming adducts with membrane proteins, leading to organ damage. Alcohol disturbed the electrolytes balance produced hypomagnesia and hypocalcemia and severely affected liver function tests.Conclusion: Magnesium levels and other related parameters could be considered as diagnostic predictors of alcohol-related toxicity. Age advances the alcohol-related health consequences, and this could be due to the cumulative effect of reduced intestinal absorption, dietary deficiencies, and alcohol toxicity.